A novel mutation in NDUFB11 unveils a new clinical phenotype associated with lactic acidosis and sideroblastic anemia. Issue 3 (25th May 2016) - Torraco, A.; Bianchi, M.; Verrigni, D.; Gelmetti, V.; Riley, L.; Niceta, M.; Martinelli, D.; Montanari, A.; Guo, Y.; Rizza, T.; Diodato, D.; Di Nottia, M.; et al.
Abstract : NDUFB11, a component of mitochondrial complex I, is a relatively small integral membrane protein, belonging to the "supernumerary" group of subunits, but proved to be absolutely essential for the assembly of an active complex I. Mutations in the X‐linked nuclear‐encoded NDUFB11 gene have recently been discovered in association with two distinct phenotypes, i.e. microphthalmia with linear skin defects and histiocytoid cardiomyopathy. We report on a male with complex I deficiency, caused by a de novo mutation in NDUFB11 and displaying early‐onset sideroblastic anemia as the unique feature. This is the third report that describes a mutation in NDUFB11, but all are associated with a different phenotype. Our results further expand the molecular spectrum and associated clinical phenotype of NDUFB11 defects. Abstract : Inactivation of CI due to a de novo mutation in NDUFB11 gene, encoding for a small and hydrophobic subunit of CI, produces a peculiar phenotype in our patient characterized by lactic acidosis and sideroblastic anemia